W stronę rytualnego chaosu – o uwodzeniu polityką w programie Kawa na ławę Bogdana Rymanowskiego - Kula, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
The text focuses on the analysis of the programme, which is categorised by the editorial team as “political journalism”. The author is trying to show her doubts regarding the lack of connection between the definition of the word ‘politics’ and anything that appears in media’s offer in such category. She points out how the broadcasters nurture in the audience the belief that the viewed programme deals with political problems and the issues of public area which are important for conscious citizens. Among the set of tools and means used throughout the programme, she highlights the following: usage of concealing type indicators, activation of keywords included in semantic fields derived from the noun ‘politics’; moving the focus from the public area to the private one; staging antagonistic scenes and critical situations. The presented tendencies to stage the reality fit into the mechanism of ‘seducing with politics’, using the citizen sphere as a pretext for focusing first and foremost on emotions, assumptions and controversies.